Pengaruh Variasi Window Width Dan Window Level Pada Lung Window Terhadap Kualitas Citra CT Scan Thorax Dengan Klinis Tumor Paru Di Rumah Sakit TK II Pelamonia Makassar - Rafika Triani Hasrianto; Ni Putu Rita Jeniyanthy; I Made Adhi Mahendrayana (Compromise Journal Community Proffesional Service Journal, 2023)
Background: Lung tumors are the growth of abnormal lumps in lung tissue which can be benign or malignant. One diagnostic imaging modality that is more supportive of lung disorders is by using a Computed Tomography Scan examination. Image manipulation can be done to improve the appearance of the image. One of the most common image processing techniques is called windowing. This technique allows the technology to change the contrast of the displayed image by adjusting the window width (Window Width) and window level (Window Level). Method: The type of research used in this research is quantitative research with a quasi-experimental approach, which aims to determine the effect of variations in window width and window level on image quality in CT scans of the Thorax with clinical lung tumors. Using variations of Window Width and Window Level WW 1000 and WL -500, -600, -700, WW 1250, WL -500, -600, -700 and WW 1550, WL -500, -600, -700. The author took CT scan data of the Thorax with clinical lung tumors in 4 samples. Then an assessment was carried out in the form of a check list by respondents, namely 3 radiographers and 1 radiologist. The data is then processed using SPSS. Results & Conclusions: There is an influence of WW 1000 and WL -500, -600, -700, WW 1250 and WL -500, -600, -700 and WW 1550 and WL -500, -600, -700 on image quality, namely artifacts and noise on Thorax CT Scan examination with lung tumor cases, the conclusion was obtained from the results of the Friedman test which showed a p.value value of <0.001 or smaller than 0.05 so that H0 was rejected and Ha was accepted. From the results of the mean rank Friedman test, it is known that the value of image quality is artifacts and noise in Thorax CT scans with lung tumor cases. Variations in window width 1550 and window level 500 are able to produce the best image quality with minimal artifacts and noise. Thorax CT scan examination in lung tumor cases.